2021
DOI: 10.1007/s11440-021-01197-7
|View full text |Cite
|
Sign up to set email alerts
|

Plane strain shear strength of unsaturated fiber-reinforced fine-grained soils

Abstract: Discrete randomly distributed fibers are commonly used to improve the engineering characteristics of the soil and thus soil properties such as shear strength, compressibility, density, and hydraulic conductivity. Most studies have so far focused on describing the behavior of soils containing randomly distributed fibers under dried or saturated conditions. However, the water table may seasonally fluctuate, thus generating unsaturated soil conditions. Therefore, a better understanding of the hydro-mechanical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…The main reason to explain the phenomenon is that with increasing of FC , the fiber number increased, which resulted in the more contact points between fiber and soil particles. Due to fibers can limit deformation of soil particles through anchoring effect, thereby result in improved the sample strength and prevent sample damage 22 , 23 .
Figure 3 Effect of FC on the stress–strain curves ( a ) FL = 4 mm; ( b ) FL = 8 mm; ( c ) FL = 12 mm; ( d ) FL = 16 mm.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main reason to explain the phenomenon is that with increasing of FC , the fiber number increased, which resulted in the more contact points between fiber and soil particles. Due to fibers can limit deformation of soil particles through anchoring effect, thereby result in improved the sample strength and prevent sample damage 22 , 23 .
Figure 3 Effect of FC on the stress–strain curves ( a ) FL = 4 mm; ( b ) FL = 8 mm; ( c ) FL = 12 mm; ( d ) FL = 16 mm.
…”
Section: Resultsmentioning
confidence: 99%
“…Tamassoki et al 22 stated that 3% content of activated carbon and coir fiber can significantly improved the compressive strength, while 2% content can remarkably enhanced the shear strength of lateritic soil. Soleimani-Fard et al 23 revealed that discrete distributed fibers can significantly improved the shear strength, compressive, and hydraulic conductivity of fiber-reinforced fine-grained soil. Malekzadeh and Bilsel 24 reported that the addition of polypropylene fiber can significantly decreased the swell-shrink of expansive soil, and shrinkage limit increased more than 50%.…”
Section: Introductionmentioning
confidence: 99%
“…With the development 1335 (2024) 012011 IOP Publishing doi:10.1088/1755-1315/1335/1/012011 2 of the fiber industry, cost-effective chemical fiber products have been increasingly used in the engineering field; thus, fiber reinforcement as a new type of geotechnical reinforcement technology has received wide attention. At present, most researchers at home and abroad have studied the influence of fiber reinforcement on the mechanical properties of sand by conducting triaxial compression tests [24][25][26][27][28], direct shear tests [29][30][31], and unconfined compressive strength tests [32][33][34][35] and have achieved interesting research results. The most commonly used fiber materials include polypropylene fibers [36][37][38][39], carbon fibers [40][41], and glass fibers [42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%